Implementation Of Work Discipline Rules For Civil Servants In Accordance With Government Regulation NO. 53/2010 Has A Significant Impact On Motivation And Performance In The Jakarta Provincial Government Environment - Hariyati Hariyati; Cecep Suhardiman (JURNAL HUKUM SEHASEN, 2024)
Government Regulation No. 53/2010 has regulated the discipline of civil servants (PNS) and requires the establishment of the Regional Personnel Agency (BKD) by regional heads to ensure the smooth implementation of ASN duties in the regions. However, the implementation of this discipline is still not optimal due to violations such as irregular attendance and leaving the office during working hours. This study aims to investigate the influence of motivation, work discipline, and career development on the performance of civil servants in DKI Jakarta. The focus is on factors that affect civil servant performance as well as the effectiveness of enforcement of disciplinary sanctions in accordance with Government Regulation No. 53 of 2010. The results show that civil servants are individuals who are appointed by authorized officials to fulfill state duties, with factors such as work culture and supervision systems affecting their performance. To improve the performance of civil servants, the government implements discipline in accordance with the regulation, which includes setting sanctions for violations of ASN discipline.